ISLAMISASI DAN INTEGRASI ILMU (Refleksi Pemikiran Studi Keislaman Kontemporer) - Lukis Alam (IAIN Ponorogo, 2016)
Abstract: Science is abstract. It means that knowledge or science is objective, structured, arranged and organized. Therefore, knowledge could not be separated because it represents factual of the truth conditions. In addition, science contains of continuity ultimate truth. Related to the religious doctrine, religious-based science is robust, whereas religion without science becomes brittle. Science and religion are interrelated and could not be separated. The perspective that said religion is higher than science is the influence of dichotomy concept of science and religion. Science is considered as human creations that have a relative truth so that it has lower position than religion.